Reconstructing a Nomadic Network: Itineraries of Jewish Actors during the First Lithuanian Independence - Pukelytė, Ina (Nordic Theatre Studies, 2015)
This article discusses the phenomenon of openness and its nomadic nature in the activities of Jewish actors performing in Kaunas during the first Lithuanian independence. Jewish theatre between the two world wars had an active and intense life in Kaunas. Two to four independent theatres existed at one time and international stars were often touring in Lithuania. Nevertheless, Lithuanian Jewish theatre life was never regarded by Lithuanian or European theatre society as significant since Jewish theatre never had sufficient ambition and resources to become such. On the one hand, Jewish theatre organized itself in a nomadic way, that is, Jewish actors and directors were constantly on the road, touring from one country to another. On the other hand, there was a tense competition between the local Jewish theatres both for subsidies and for audiences. This competition did not allow the Jewish community to create a theatre that could represent Jewish culture convincingly. Being a theatre of an ethnic minority, Jewish theatre did not enjoy the same attention from the state that was given to the Lithuanian National Theatre. The nomadic nature of the Jewish theatre is shown through the perspective of the concept of nomadic as developed by Deleuze and Guattari.